The Peruvian intellectual influence in the development of the woman paper on the beginnings of the twenty century - Díaz Manunta, Janet (2020)
The intention of this article is to revise women’s journalistic literature at the beginning of the twentieth century. This in an instrument of analysis of the collective thinking that the intellectual woman owned, and, that caused —directly or indirectly— the future sociocultural changes. During the two first decades of the twentieth century, the intellectual women worked on a crux subject: woman’s access to education and to a decent job. This central theme was considered since several points of view, which created discussions and arguments between the same writers. This study revolves around of Mercedes Cabello de Carbonera’s article, “The exams”.